How Self-Perceptions of Identity Change in Person, Role, and Social Identities Relate to Depression. Issue 4 (2nd October 2017) - Carter, Michael J.
ABSTRACT: This study uses a cross-sectional research design to examine how individuals perceive recent experiences of identity change in various person, role, and social identities. Specifically addressed is how self-perceptions regarding the magnitude and direction of one's experience of identity change relate to depression. A survey was administered to 854 study participants that measured perceived changes in 12 discrete identities (four person, four role, and four social identities) over a 6-month period. The results reveal that the more severe one perceives their experience of identity change to be, the greater their level of depression. However, generally, when one perceives that the direction of their identity change is progressive (rather than regressive), they are less likely to be depressed.